(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
In recent years, a large number of different methodologies and forms of advanced training outside of classes in a preschool institution have appeared in the education system for working with children with disabilities. The relevance of this article lies in identifying the latest trends in the field of additional education, identifying effective ways to correct and rehabilitate children.